Analysis of Factors in the Use of Traditional Care for Postpartum Women - Mursal, Mursal; Akbar, Yudi; Rizana, Novia (Journal of Language and Health, 2024)
Traditional medicine is a material or concoction in the form of plants, animals, minerals, extracts, or mixtures of these materials that have been used for treatment for generations and can be applied according to the norms prevailing in society. Postpartum is a period where a mother after giving birth, namely where the mother's body adapts after giving birth. The postpartum period is 6-8 weeks after giving birth. During the postpartum period, mothers experience many psychological changes to face the postpartum period which can increase the risk of health problems for the mother. Issues that are often experienced by postpartum mothers and cause pain during the postpartum period include wounds in the perineum area that occur during the labor process. The purpose of the study was to determine how traditional care is applied to postpartum mothers. The design of this study was a cross-sectional study. The population in this study were all postpartum mothers totaling 55 respondents using the total respondent technique. Data was collected using a questionnaire and analyzed univariately and bivariately. The results of the study showed that the application of traditional care to postpartum mothers was in the category applied by 39 respondents (70.9%) and the type of application of conventional care to postpartum mothers that was most widely applied was manoe-peut-ploh-peut by 48 respondents (87.2%) and the least applied was madeung massage therapy by 30 respondents (54.5%). It is expected that postpartum mothers who use traditional medicine will consult with health workers to avoid side effects and other dangers from the application of conventional care.